Computer-supported interaction for composing documents logically. (2nd February 2009) - Watanabe, Toyohide; Kato, Kei
Document preparation can be typically regarded as one of human beings' intelligent activities. Creative and logical abilities, derived personally from explicit motivations, rich knowledge, useful experiences, etc., take up important roles to make well-structured and story-oriented documents understandable and readable. Thus, it is not always easy for beginners to compose documents such as reports, papers and articles successfully and effectively. In this paper, we address a computer-supported environment to compose documents logically: namely, we propose a framework for composing logically organised documents. The main idea is to formulate the composition process as the working procedure of a query list and logic tree. The query list defines what should be discussed in the document, while the logic tree specifies how to write the topics/sub-topics. This paper discusses these roles in the composition process and then reports the manipulation interface on the prototype system.